2011
DOI: 10.1021/la203657n
|View full text |Cite
|
Sign up to set email alerts
|

Redox Grafting of Diazotated Anthraquinone as a Means of Forming Thick Conducting Organic Films

Abstract: Thick conductive layers containing anthraquinone moieties are covalently immobilized on gold using redox grafting of the diazonium salt of anthraquinone (i.e., 9,10-dioxo-9,10-dihydroanthracene-1-diazonium tetrafluoroborate). This grafting procedure is based on using consecutive voltammetric sweeping and through this exploiting fast electron transfer reactions that are mediated by the anthraquinone redox moieties in the film. The fast film growth, which is followed by infrared reflection absorption spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
65
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(75 citation statements)
references
References 47 publications
10
65
0
Order By: Relevance
“…In our experimental grafting conditions, the ClAQ surface coverage for the modified carbon material was estimated to about only 25% of that expected for a monolayer. 12 Since the surface coverage of AQ molecules electrochemically grafted varies linearly with film thickness up to a surface concentration of 10 © 10 ¹9 mol cm ¹2 , 19 one can consider that all AQ molecules are electroactive and postulate that this is also the case for a low surface coverage such as the one estimated for the ClAQ-modified carbon. Finally, surface functionalization enables an increase of the specific capacitance of the modified electrode by a factor of two (from 110 to 206 F/g) compared to pristine carbon electrode.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our experimental grafting conditions, the ClAQ surface coverage for the modified carbon material was estimated to about only 25% of that expected for a monolayer. 12 Since the surface coverage of AQ molecules electrochemically grafted varies linearly with film thickness up to a surface concentration of 10 © 10 ¹9 mol cm ¹2 , 19 one can consider that all AQ molecules are electroactive and postulate that this is also the case for a low surface coverage such as the one estimated for the ClAQ-modified carbon. Finally, surface functionalization enables an increase of the specific capacitance of the modified electrode by a factor of two (from 110 to 206 F/g) compared to pristine carbon electrode.…”
Section: Resultsmentioning
confidence: 99%
“…This might not be always the case as previously demonstrated for nitrophenyl-modified carbon 18 and although the surface coverage of an electrochemically modified Au electrode with anthraquinone groups was found to vary linearly with film thickness. 19 Secondly, in one of our recent study, the electrochemical behavior of anthraquinone-modified Black Pearls was investigated in electrolyte of various pHs ranging from acidic (0.1 M H 2 SO 4 ) to alkaline (0.1 M KOH) media. 15 It was found that the voltammetric charge varied significantly between these two electrolytes.…”
mentioning
confidence: 99%
“…Redox grafting parameters, such as scan rate, switching potentials, and number of cycles, are chosen accordingly to Ref. [32] in order to obtain a thin molecular layer (∼1-10 nm) even for high number of cycles (N > 10). This method ensures the formation of a robust and thin layer of AQ molecules bonded covalently to the electrode [32][33][34][35].…”
Section: Sample Fabrication and Methodsmentioning
confidence: 99%
“…[32] in order to obtain a thin molecular layer (∼1-10 nm) even for high number of cycles (N > 10). This method ensures the formation of a robust and thin layer of AQ molecules bonded covalently to the electrode [32][33][34][35]. In the present case, for 20 voltammetry cycles the total AQ thickness is estimated by atomic force microscopy (AFM) to be ∼8 nm.…”
Section: Sample Fabrication and Methodsmentioning
confidence: 99%
“…Recently, a new method called redox grafting was proposed for formation of thick covalently attached conducting organic layers on different substrates (GC, gold, and stainless steel) via electrochemical reduction of various aryldiazonium salts (e.g., 9,10-dioxo-9,10-dihydroanthracene-1-diazonium salt) [48][49][50]. A prerequisite for redox grafting is that the aryldiazonium salt used should contain a redox active functionality.…”
Section: à2mentioning
confidence: 99%